Effect of grain boundary resistance on the ionic conductivity of amorphous xLi2S-(100-x)LiI binary system - Di, Longbang; Pan, Jiangyang; Gao, Lei; Zhu, Jinlong; Wang, Liping; Wang, Xiaomeng; Su, Qinqin; Gao, Song; Zou, Ruqiang; Zhao, Yusheng; Han, Songbai (Frontiers in Chemistry, 2023)
Solid-state electrolytes (SSEs) hold the key position in the progress of cutting-edge all-solid-state batteries (ASSBs). The ionic conductivity of solid-state electrolytes is linked to the presence of both amorphous and crystalline phases. This study employs the synthesis method of mechanochemical milling on binary xLi2S-(100-x)LiI system to investigate the effect of amorphization on its ionic conductivity. Powder X-ray diffraction (PXRD) shows that the stoichiometry of Li2S and LiI has a significant impact on the amorphization of xLi2S-(100-x)LiI system. Furthermore, the analysis of electrochemical impedance spectroscopy (EIS) indicates that the amorphization of xLi2S-(100-x)LiI system is strongly correlated with its ionic conductivity, which is primarily attributed to the effect of grain boundary resistance. These findings uncover the latent connections between amorphization, grain boundary resistance, and ionic conductivity, offering insight into the design of innovative amorphous SSEs.